UPACARA TRADISI MERON RELEVANSINYA DENGAN KEHIDUPAN MASYARAKAT DESA SUKOLILO KABUPATEN PATI (JPP, 2011)
Traditional ceremony Meron in Sukolilo is a unique and specific culture of nation. Valuesand meanings contained in the ritual have become relevant to social life. At present,the values of traditional ceremony Meron have undergone changes and shifts, then worriedthat it will become extinct. The method of this study is qualitative. Location of thestudy is in Sukolilo village, Pati regency. Target of the study is traditional ceremonyMeron. Data collection methods are observation, interview and documentation. Datavalidation is defined through cross-recheck. And data analysis implements interactiveapproach from Miles and Huberman. The result of the study: (1) the physical model andceremony of traditional ceremony Meron reflects functions of manifest and latent. (2)values contained in traditional ceremony Meron are historic, social, religious, pedagogic,and esthetic. (3) the value changes in traditional ceremony Meron happened because ofglobalization and modernization, while essence of the original model and process stillmaintained. The changes only happened in additional event such as entertainment. Carnivalcelebration has also undergone changes.. (4) Existence of traditional ceremonyMeron is very relevant to social life because it has inculturated and become part of sociallife. Existence of traditional ceremony Meron is able to be a trigger to support the developmentof social life in all major: ideology, politic, economy, social, culture, defense andsecurity.Keyword: Traditional Ceremony, Meron, Values